Assessment of a semi-quantitative screening method for diagnosis of ethylene glycol poisoning. (July 2017) - Sankaralingam, Arun; Thomas, Annette; James, David R; Wierzbicki, Anthony S
Background: Ethylene glycol poisoning remains a rare but important presentation to acute toxicology units. Guidelines recommended that ethylene glycol should be available as an 'urgent' test within 4 h, but these are difficult to deliver in practice. This study assessed a semi-quantitative enzymatic spectrophotometric assay for ethylene glycol compatible with automated platforms. Methods: The ethylene glycol method was assessed in 21 samples from patients with an increased anion gap and metabolic acidosis not due to ethylene glycol ingestion, and seven samples known to contain ethylene glycol. All samples were analysed in random order in a blinded manner to their origin on a laboratory spectrophotometer. Results: In this study, seven samples were known to contain ethylene glycol at concentrations >100 mg/L. The method correctly identified all seven samples as containing ethylene glycol. No false-positives were observed. Thirteen samples gave clear negative results. Ethylene glycol was present at <20 mg/L in one sample, but this sample remained within the limits of the negative control. Passing-Bablock correlation of estimates of ethylene glycol concentration against results obtained when the samples had been analysed using the quantitative method on an automated analyser showed a good correlation (R = 0.84) but with an apparent under-recovery. Conclusions: A semi-quantitative assay for ethylene glycol was able to discriminate well between samples containing ethylene glycol and those with other causes of acidosis. It is a practical small-scale assay for rapid identification of cases of ethylene glycol poisoning.